Information Technology in Disaster Risk Reduction : 4th IFIP TC 5 DCITDRR International Conference, ITDRR 2019, Kyiv, Ukraine, October 9–10, 2019, Revised Selected Papers /: 4th IFIP TC 5 DCITDRR International Conference, ITDRR 2019, Kyiv, Ukraine, October 9–10, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available